REALITY ORIENTATION MODEL FOR MENTAL DISORDER PATIENTS WHO EXPERIENCE AUDITORY HALLUCINATIONS - Arum Pratiwi; Enita Dewi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2016)
Introduction: The number of patients with mental illness is increasing every year. The research aim was to develop a model of reality orientation therapy in patients with schizophrenia who had auditory hallucinations. Methods: This design of the study was a sequential exploratory research study which combined qualitative and quantitative approaches. The respondents involved in this study were patients with schizophrenia who experienced auditory hallucinations. Ten respondents who met the criteria were used as the population target in the therapeutic procedure trial. Five nurses who had experience treating patients in a mental hospital were established as experts in the trial instrument development. Initially, the content of the hallucinations were identified using "Beliefs about the Voices Questionnaire (BaVQ)" through interviews. These answers were then analyzed using thematic analysis. Results: The level of the patient's anxiety was statistically significant at 1.078 (P 0.309). It can be concluded that there was no difference between the patient's anxiety before and after cognitive therapy focused on reality orientation. Discussion: The model should be more elaborate when applied to patients who experience negative auditory hallucinations.